Al-Irsyad Association and Al-Irsyad Al-Islamiyyah in Islamic Education - Nurhidayat, Wachid (Letiges, 2024)
As an organization that has been around for a long time, it cannot be denied that Al-Irsyad continues to experience changes in line with the social, economic and political dynamics that occur in Indonesia. The division peaked in 2007, then splitting the organization into the Al-Irsyad Association and Al-Irsyad Al-Islamiyyah. This phenomenon is interesting, so the aim of this research is to look further at changes in the orientation of Al-Irsyad's Islamic education. This study uses qualitative ethnographic methods. Most of the data was obtained from observations and interviews in the field, which were then supported by secondary data from various sources. Data analysis using the Spradley model includes domain analysis, taxonomic analysis, componential analysis, and model analysis. The results of the study show that the Al-Irsyad Association and Al-Irsyad Al-Islamiyyah institutions in identifying themselves, each institution carries out different strategies as a manifestation of educational orientation based on the interpretation of Mabadi Al-Irsyad. Islamic educational institutions under the auspices of Al-Irsyad Al-Islamiyyah gave rise to schools with a modern-exclusive style, and educational institutions under the aegis of the Al-Irsyad Association had a more puritanical-inclusive kind. The differences in values that are the guidelines or ideologies of each institution are formed over time and social, political, economic and cultural dynamics.